Near Infrared -Visible Photonic Bandgap in One-Dimensional Periodic Photonic Crystal Structure Composed of Tio2/Te Layers - Khalid, Shalaw Saman; Abdulkareem, Sarkew Salah; Ahmed, Sana Latif; Talib, Sana Dishad; Ghidan, Shahla Ahmed (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2023)
In this present paper, we consider some features of the states of one-dimensional photonic crystals. Form the numerical results performed by transfer matrix method in periodic multilayer structure made of titanium dioxide and tellurium material, it is found that the structure possesses a photonic band gap it was determined that the structure has a photonic band gap in the borderline visible and infrared spectral region. Our predictions were in good agreement with the photonic bandgap tuning. Our simple model can also predict and explain the effect of incidence angle and wavelength and number of layers on the photonic bandgap. We expect such structures to play an important role in micromechanical tunable optical sensors and filters.